Guidelines for Subject Analysis in Subject Cataloging - Redigolo, Franciele Marques; Lopes Fujita, Mariângela Spotti [UNESP]; Gil-Leiva, Isidoro (Taylor & Francis, 2022)
The representation of information in subject cataloging as a result of subject analysis will depend on the cataloger’s prior knowledge, influenced by subjectivity. The subject analysis in cataloging is a central theme of this investigation with the aim to elaborate guidelines for subject analysis in cataloging. For this purpose, how books are cataloged in university libraries has been verified. The Individual Verbal Protocol was applied with catalogers from Brazilian and Spanish University Libraries. Directions for the elements and variables of the subject analysis and procedures for good development were obtained to constitute the Guidelines of Subject Analysis in Cataloging. It is concluded that the guidelines formed by four sections are indicated for incorporation in subject cataloging procedure manuals for the purpose of improving the levels of representation and information retrieval results.
Keywords: individual verbal protocol; subject analysis; Subject cataloging